PENDAMPINGAN MANAJEMEN SUKSES UJIAN NASIONAL (UN) UNTUK KKM MALANG SELATAN (MTsN Harjokuncaran Sumbermanjing Wetan sebagai Inti) - Meinarni Susilowati (El-QUDWAH, 2010)
This present paper aims at reporting a collaborative research on empowering teachers’ competence and skill in helping their students to face the National Examination (NE). Considering its role in determining whether a student can pass a particular level of education, this high stake test creates wide negative impacts on students, teachers, and parents. It has been generally noted that some teachers have done irrespective efforts to make their students pass the grade level because of, among other, their lack of competence and skill to create conducive teaching learning processes. This present participatory action research accommodated this need by providing the teachers three cycles to help them effectively prepare the students face the NE. The findings showed that the teachers’ competence and skill in adapting and adopting the test items tended to significantly improve. In addition, this improvement was indicated to influence, to a particular extent, the number of students who passed the NE. However, the conclusion should be cautiously made considering the fact that some factors were significant in influencing the improvement.